2021
DOI: 10.1002/pro.4026
|View full text |Cite
|
Sign up to set email alerts
|

Structure of human BCCIP and implications for binding and modification of partner proteins

Abstract: BCCIP was isolated based on its interactions with tumor suppressors BRCA2 and p21. Knockdown or knockout of BCCIP causes embryonic lethality in mice. BCCIP deficient cells exhibit impaired cell proliferation and chromosome instability. BCCIP also plays a key role in biogenesis of ribosome 60S subunits. BCCIP is conserved from yeast to humans, but it has no discernible sequence similarity to proteins of known structures. Here we report two crystal structures of an N‐terminal truncated human BCCIPβ, consisting o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…S2A). Strikingly, the structure showed that BCCIPα adopts a structural fold that is completely different from the structure of BCCIPβ published previously (see details below) ( 34 , 35 ). Analyses of this structure allowed us to design a new construct, BCCIPα-ΔL, containing a larger deletion (residues 231 to 280) of a long disordered loop (fig.…”
Section: Resultscontrasting
confidence: 81%
See 3 more Smart Citations
“…S2A). Strikingly, the structure showed that BCCIPα adopts a structural fold that is completely different from the structure of BCCIPβ published previously (see details below) ( 34 , 35 ). Analyses of this structure allowed us to design a new construct, BCCIPα-ΔL, containing a larger deletion (residues 231 to 280) of a long disordered loop (fig.…”
Section: Resultscontrasting
confidence: 81%
“…The previously published structures of BCCIPβ from human and yeast both exhibit a fold similar to GCN-5-related acetyltransferases, characterized by a splayed seven-stranded β sheet that is surrounded by several α helices on each side (Fig. 4A) (34,35). BCCIPβ is, however, unlikely an acetyltransferase because it lacks the catalytic residues conserved in those enzymes (34,35).…”
Section: Unique Fold Of Bccipαmentioning
confidence: 82%
See 2 more Smart Citations